Pengaruh Stres Lingkungan Kerja, Stres Kerja Organisasi Dan Stres Kerja Pribadi Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Barito Selatan: The Effect of Environmental Work Stress, Organizational Work Stress and Personal Work Stress on Employee Performance in The Department of Population and Civil Registration of South Barito District - Kurniaty, Harlina (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
This research aims to determine the effect of Environmental Work Stress, Organizational Work Stress and Personal Work Stress on Employee Performance in the South Barito District Population and Civil Registry Office by 2020 and to find out and district which variables have the most effect on Environmental Work Stress, Organizational Work Stress and Personal Work Stress on Employee Performance in the South Barito District Population and Civil Registry Office by 2020. The theory used in this study is that work stress according to Robbins and Judge (2016:425) three main sources can cause the onset of stress, namely environmental factors, organizational factors and personal factors and employee performance theory according to Agus Dwiyanto (2017:47) there are several indicators usually used to measure the performance of public bureaucracy namely productivity, service quality, responsiveness, responsibility, and accountability. The study used quantitative descriptive methods with data collection techniques using observations, interviews, documentation, and questionnaires. The data analysis tool used is Multiple Linear Regression using SPSS Version 25. The result obtained in multiple linear regression calculations is Y = 2.547 + 0.762X1 + 1.438X2 + 0.708X3 where the value (a) is 2.547 and the coefficient value (b1) is 0.762 the coefficient value (b2) is 1,438 and the coefficient value (b3) is 0.708. Then obtained the results of thitung from the above test that thitung > table (3,372 > 2,060) then Ho rejected and H1 received, meaning variable X1 or Environmental Work Stress partially affects the Performance of Employees of the Civil Office of South Barito Regency. Then for variable X2 thitung > ttabel (8,577 > 2,060) then Ho is rejected and H2 is accepted, meaning variable X2 or Organizational Work Stress partially affects the Performance of Residents Office Employees and Civil Recording of South Barito Regency. And for variable X3 thitung > ttabel (3,477 > 2,060) then Ho was rejected and H3 was accepted, meaning variable X3 or Personal Work Stress partially affects the Performance of Residents Office Employees and Civil Registry of South Barito Regency.